P58 A Comparison Between The Clinical Features Of Pisz And Pizz Patients With Alpha-1 Antitrypsin Deficiency. (10th November 2014) - Vayalapra, S; Edgar, RG; Griffiths, D; Stockley, RA; Turner, AM
Abstract : Introduction: Alpha-1 antitrypsin deficiency (AATD) is a hereditary disorder affecting about 1 in 3000 people in the UK commonly associated with early-onset emphysema. There are two common deficiency alleles - PiS and PiZ. PiZZ patients have severe AATD, with levels of 10–15% normal. PiSZ patients have less severe deficiency (≈ 40% normal) and are generally thought to have a minimal risk. We hypothesised that if PiSZ patients were at lower risk of COPD than PiZZ, and their lung disease would be more characteristic of usual COPD than that of PiZZ patients. Method: 104 PiSZ patients and 638 PiZZ patients from the UK AATD registry (ADAPT) were compared for their demographics, lung function, risk factors for COPD (e.g. smoking, occupation), co-morbidities associated with COPD, index status (i.e. if diagnosed due to lung disease or family screening) and CT densitometry (where available). Outcome in terms of lung function decline and mortality was also assessed. Univariate statistics were used to guide subsequent regression analyses. Results: Emphysema was more likely in PiZZ than PiSZ patients (OR 11.0 (5.7–21.3); p < 0.001) in the regression analysis after accounting for age, pack years and lung index status. PiZZ patients also had significantly worse FEV1 and DLCO than PiSZ patients in similar regression models (both p < 0.01). Emphysema was more severe in both upper and lower zone (both p < 0.01), and proportionately greater in the lower zone (UZ/LZ VI = 1.5 v 1.2) in PiZZ patients. Mortality and DLCO decline were also greater in PiZZ patients. Conclusion: PiSZ patients have a milder form of AATD associated with better lung function. The data suggests the pattern of emphysema is closer to usual COPD than classical AATD. Further analyses comparing PiSZ to PiMM are now ongoing.